Time-intensity and reaction-time methodology applied to the dynamic perception and liking of bitterness in relation to body mass index - León Bianchi, L. (2018)
Fil: León Bianchi, L. Pontificia Universidad Católica Argentina. Facultad de Ingeniería y Ciencias Agrarías; Argentina